2019
DOI: 10.3390/ijms20153654
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Cells and Toll-like Receptor–Dependent Responses at the Maternal–Fetal Interface

Abstract: During pregnancy, the placenta, the mother and the fetus exploit several mechanisms in order to avoid fetal rejection and to maintain an immunotolerant environment throughout nine months. During this time, immune cells from the fetal and maternal compartments interact to provide an adequate defense in case of an infection and to promote a tolerogenic milieu for the fetus to develop peacefully. Trophoblasts and decidual cells, together with resident natural killer cells, dendritic cells, Hofbauer cells and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 180 publications
(201 reference statements)
0
43
0
Order By: Relevance
“…This reflects a state of enhanced innate immune vigilance against infection: neutrophils, the most abundant of all human phagocytes, are recruited to sites of infection or injury by chemokines such as complement C5a and form the first line of defense against microbial challenge. Engulfed micro-organisms are internalized in phagolysosomes and destroyed using a wide range of effector mechanisms including release of serine proteases (e.g., neutrophil elastase, cathepsin G) and production of reactive oxygen species (141,169). Pathogens that evade phagocytosis can be controlled by the release of neutrophil extracellular traps (NET), large reticular structures containing cytotoxic granule proteins and AMP that sequester and neutralize microbes (170).…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects a state of enhanced innate immune vigilance against infection: neutrophils, the most abundant of all human phagocytes, are recruited to sites of infection or injury by chemokines such as complement C5a and form the first line of defense against microbial challenge. Engulfed micro-organisms are internalized in phagolysosomes and destroyed using a wide range of effector mechanisms including release of serine proteases (e.g., neutrophil elastase, cathepsin G) and production of reactive oxygen species (141,169). Pathogens that evade phagocytosis can be controlled by the release of neutrophil extracellular traps (NET), large reticular structures containing cytotoxic granule proteins and AMP that sequester and neutralize microbes (170).…”
Section: Neutrophilsmentioning
confidence: 99%
“…Decidual DC (dDC) account for <2% of decidual leukocytes, are a highly proliferative and relatively immature population, and are phenotypically distinct from peripheral DC: they display a universal reduction in expression of T cell costimulatory molecules and thus fail to induce specific T cell responses in vitro (189). dDC help to prevent fetal rejection by promoting tolerogenic responses to endocytosed trophoblast antigens, recruit NK cells through production of IL-15 and potentiate decidual angiogenesis via close dialogue with decidual stromal cells (141).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are important regulators in both the adaptive and innate immune responses. [10][11][12] They are capable of inducing antitumor mediators and are highly expressed on antigen-presenting cells. TLRs selectively recognize a variety of conserved molecular structures in invading pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…During the first trimester of pregnancy NK cells represent the most abundant immune cell population in decidual tissue (105). However, whether decidual NK cells are derived from peripheral NK cells that enter the fetal-maternal interface and convert into the decidual phenotype and/or expand from residual NK cells is not finally resolved (106,107). Recently, it was suggested that under the influence of P4 and IL-15, peripheral NK cells start to proliferate, migrate into the implantation site along chemotactic and hormonal gradients provided by trophoblast and endometrial cells and finally convert into decidual NK cells due to high levels of local TGF-β and IL-11 (106).…”
Section: Natural Killer Cellsmentioning
confidence: 99%